Critical approaches to ancient Near Eastern art - Brown, Brian A. (Brian Ashley); Feldman, Marian H. (De Gruyter, 2014)
Critical Approaches to Ancient Near Eastern Art concentrates on the visual, material, and built aspects of the Ancient Near East from the fourth millennium BCE to the Hellenistic period. Presenting innovative theoretical approaches to Ancient Near Eastern art history, this volume will be of value to scholars of the Ancient Near East, as well as to those interested in contemporary art historical and anthropological approaches to visual culture.